A combined method for binning coupling angles to define coordination patterns. (16th April 2020) - Beitter, John; Kwon, Young-Hoo; Tulchin-Francis, Kirsten
Abstract: The vector coding technique has been used to quantify coordination of two joints, segments, and/or planes during cyclic activities, such as walking. Coordination patterns can be identified by categorizing the tangent lines of an angle-angle plot by their direction, termed "coupling angle binning" or "phase binning". In the literature the ranges of directions, or "bins", originally divided by Chang et al. and more recently by Needham et al. have different strengths. Chang's method identifies general patterns with large bins while Needham's method identifies a dominant joint or segment in the pattern. This study created a novel method that incorporates bin categories from both methods, and therefore recognizes both general patterns and a dominant contributor when appropriate. This new method, the SRC method, as well as the two existing methods, were used to quantify knee-ankle coordination in the sagittal plane for healthy individuals and an individual with clubfoot during gait. Similarities and differences in classification between methods were compared and further investigated by interpreting the uncoupled angular data. Each method was then used to evaluate sagittal-coronal coordination of the forefoot in an individual with clubfoot during gait. This was done to demonstrate across-plane coordination analysis, to confirm that the advantages of the combined method extend to coupling pairs with like ranges of motion, and to present a clinical application. It was found that the TSRH binning methods provides a more complete description of coordination by including coordination categories defined by both the Chang and Needham method.